A maximal rowing-ergometer protocol to predict maximal oxygen uptake in female rowers - Mazza, O. B.; Gam, S.; Kolind, M. E.; Kiær, C.; Donstrup, C.; Jensen, K. (International Journal of Sports Physiology and Performance, 2023)
Background: Laboratory assessment of maximal oxygen uptake (VO2max) is physically and mentally draining for the athlete and requires expensive laboratory equipment. Indirect measurement of VO2max could provide a practical alternative to laboratory testing. Purpose: To examine the relationship between the maximal power output (MPO) in an individualized 7 × 2-minute incremental test (INCR-test) and VO2max and to develop a regression equation to predict VO2max from MPO in female rowers.